Does chemical shift imaging offer a biomarker for the diagnosis and assessment of disease severity in multiple myeloma?: A cross-sectional study. Issue 6 (12th February 2021) - Takasu, Miyuki; Tanitame, Keizo; Baba, Yasutaka; Akiyama, Yuji; Tamura, Takayuki; Kondo, Shota; Maeda, Shogo; Sakai, Akira; Awai, Kazuo
Abstract : Abstract: To investigate whether chemical shift imaging (CSI) is useful for differentiating myelomatous infiltration from hematopoietic bone marrow (BM) and for quantitatively assessing disease severity. In this retrospective study, spinal MRI, including a sagittal iterative decomposition of water and fat with echo asymmetry and least-squares estimation T2 fast spin-echo sequence, was performed on 76 myeloma patients (45 men, 67.0 ± 11.4 years; 31 women, 66.5 ± 11.0 years) and 30 control subjects (20 men, 67.0 ± 8.4 years; 10 women, 67.0 ± 9.2 years). The fat-signal fraction (FF) and mean signal dropout ratio (DR) were calculated from lumbar BM that contained no focal lesions. The BM plasma cell percentage (BMPC%) and serological data were obtained. As DR is highest when FF = 50%, the patients were divided into 2 groups: a water-dominant group (FF < 50%) and a fat-dominant group (FF > 50%). Serum monoclonal protein (M protein), β2-microglobulin, and BMPC% were significantly higher in the water-dominant group than in the fat-dominant group. In the water-dominant group, DR correlated significantly with BMPC% and M protein, whereas in the control group, DR showed a weak correlation with age but no correlation with other clinical factors. No significant differences in any clinical data were seen between high and low DR. CSI proved ineffective for differentiating myelomatous infiltration from hematopoietic BM. For myeloma patients with relatively high BM cellularity, a small signal drop on opposed-phase images indicated a higher tumor burden. For BM with relatively low cellularity, disease severity was not reflected by CSI.